Efficacy Of Ondansetron, Granisetron And Palonosetron On Post operative Nausea and Vomiting in Patients undergoing Elective Neurosurgical Procedure - Vasudha Govil; Richa Malik; Prashant Kummar; Anju Rani; Sudha Puhal (Basrah Journal of Surgery, 2025)
Background Neurosurgery is associated with high incidence of PONV. 5HT3 Antagonists are highly specific for the treatment of nausea and vomiting. They are preferred antiemetic agents in neurosurgeries due to the lack of sedation and extrapyramidal reactions. The aim of the study is to compare the effect of ondansetron, granisetron and palonosetron on postoperative nausea and vomiting in patients undergoing craniotomy under general anaesthesia. Material and methods A total of 75 adult patients, of either sex, age group of 18-60 years, belonging to ASA I, II and III, scheduled to undergo elective neurosurgical procedure, under general anaesthesia, were enrolled in the prospective, randomized, double blind study. Anaesthesia was induced with fentanyl 2 µgkg-1 and propofol 2 mgkg-1 and vecuroniun bromide 0.1 mgkg-1 was given to facilitate endotracheal intubation. At the time of dura closure, patients were randomly allocated to one of the three groups (n=25 each) Group O: to receive injection ondansetron 4 mg i/v, Group G: to receive injection granisetron 1 mg i/v and Group P: to receive injection palonosetron 0.075 mg i/v. Observer recorded episode of nausea and vomiting, use of rescue antiemetics, degree of satisfaction and variation in ECG post operatively. Results The cumulative incidence of PONV in 0 to 48 hrs postoperatively was 57.33%. The incidence of PONV amongst the three groups is statistically significant with the least incidence in Group P (p